Antispasmodics basic esters of substituted α-phenyl and α-cyclohexylpropionic or acetic acids and of substituted malonic acids - Abcede, Juanito Beltran
During this investigation a number of substituted α-phenyl- and α-cyclohexyl-β-hydroxypropionic acids, RR'C(OH)CHR''COOH, were prepared (R and R' = methyl, amyl, hexyl, tetramethylene, hexamethylene or 3-methylhexamethylene; R'' = phenyl or cyclohexyl). The substituted α-phenyl-β-hydroxypropionic acids were obtained by the interaction of the chloromagnesium salt of phenylacetic acid, C6H5CH(MgCl)COOMgCl, with the required ketone (Ivanov reaction). α-Phenyl-α-(l-hydroxycyclopentyl)-acetic acid (α-phenyl-β-β-tetrametylene-β-hydroxypropionic acid) and α-phenyl-α-(l-hydroxycycloheptyl) acetic acid were hydrogenated catalytically to the corresponding α-cyclohexyl acids.